Palaeoenvironmental evolution of Vigla western Naxos (Cyclades, Greece), depositional environment and sea level changes in Upper Holocene. - Evelpidou, N.; Pavlopoulos, K.; Vassilopoulos, A.; Triantafyllou, M.; Vouvalidis, K.; Syrides, G. (European Geosciences Union, General Assembly, 2010)
The study area of Vigla coastal zone is located at the W coast of Naxos, the largest island of Cycladic plateau. The study of sea-land interactions during Holocene in relation to the eustatic sea level oscillations as well as the geomorphologic observations and analyses on deposited sediments, aims to reveal the paleogeographic evolution of the landscape and its impact to the overall cultural development of the area. A geomorphological mapping of the coastal area along with the drilling of three boreholes has been accomplished. Moreover, a micro faunal analysis has been performed. Five samples of plant material, chart coal and shells were dated using AMS and Conventional radiocarbon techniques providing temporal control of the sediments. Sea level rise along with sea-land interactions to the landscape evolution and the transgression of sea in 5000 BP have been verified.